ケイコウ Xセン ブンセキ ソウチ ニヨル ガンセキ ノ テイリョウ カガク ブンセキ(1)シュヨウ ゲンソ - 本吉, 洋一; モトヨシ, ヨウイチ; 白石, 和行; シライシ, カズユキ; Motoyoshi, Yoichi; Shiraishi, Kazuyuki (1995)
P(論文) 国立極地研究所に新たに導入された蛍光X線分析装置(理学電機工業製, RIX3000)による岩石試料中の主要元素(Si, Ti, Al, Fe, Mn, Mg, Ca, Na, K, P)の定量化学分析について, 分析の概要, 注意点などをまとめた。また, 検量線法, マトリックス補正法, ファンダメンタル・パラメーター(FP)法による分析結果を比較した。特異な組成の岩石(超塩基性岩, 炭酸塩岩, 石英の非常に多い岩石など)を除く通常の組成の岩石試料については, これら方法の組み合わせにより, 精度良く分析できることがわかった。 Analytical procedures for major elements in rocks (Si, Ti, Al, Fe, Mn, Mg, Ca, Na, K, P), using a newly installed X-ray fluorescence analyzer (RIGAKURIX3000) at the National Institute of Polar Research, are summarized. The calibration curve method, the matrix correction method, and the fundamental parameter method are compared with respect to accuracy. By combining these methods, rocks with normal compositions, excluding ultramafic rocks, carbonate rocks and extremely quartz-rich rocks, can be quantitatively analyzed accurately. departmental bulletin paper